2001
DOI: 10.1161/hh2301.100812
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Sympathetic Nervous Activity in Mice Deficient in αCGRP

Abstract: Abstract-␣-Calcitonin gene-related peptide (␣CGRP) is a pleiotropic neuropeptide implicated in a variety of physiological processes. To better understand the biological functions of ␣CGRP, we developed an ␣CGRP-null mouse model using a gene targeting approach. Recordings of mean arterial pressure (MAP) and heart rate (HR) showed that basal MAP and HR were significantly higher in both anesthetized and conscious, unrestrained ␣CGRP-null mice than in corresponding wild-type mice. The elevated MAP in ␣CGRP-null mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
118
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 149 publications
(124 citation statements)
references
References 25 publications
6
118
0
Order By: Relevance
“…It is yet to be determined whether this NANCdependent physiological antagonism of sympathetic/ parasympathetic tone is caused by a direct vascular effect of CGRP and/or through the interference of this neuropeptide with noradrenaline/acetylcholine release from perivascular nerve terminals. In support of the latter concept, Oh-hashi et al (2001) have reported increased urinary levels of catecholamine metabolites in mice lacking the aCGRP gene. In contrast, Maynard and Burnstock (1994) have shown that purines but not CGRP act as the main pre-junctional modulator of tritiated noradrenaline release in the rabbit ear artery model.…”
Section: Discussionmentioning
confidence: 85%
“…It is yet to be determined whether this NANCdependent physiological antagonism of sympathetic/ parasympathetic tone is caused by a direct vascular effect of CGRP and/or through the interference of this neuropeptide with noradrenaline/acetylcholine release from perivascular nerve terminals. In support of the latter concept, Oh-hashi et al (2001) have reported increased urinary levels of catecholamine metabolites in mice lacking the aCGRP gene. In contrast, Maynard and Burnstock (1994) have shown that purines but not CGRP act as the main pre-junctional modulator of tritiated noradrenaline release in the rabbit ear artery model.…”
Section: Discussionmentioning
confidence: 85%
“…Because the calcitonin gene was also knocked out in the mice, it is not certain whether the phenotypes of the mutant mice were by the loss of CGRP, calcitonin, or both. Recently, a third strain of ␣CGRP-deficient mice has been developed by Oh-hashi et al (24). The knockout mice have significantly higher mean arterial pressure as well as HR than the WT mice.…”
Section: Discussionmentioning
confidence: 99%
“…We generated CGRP knockout mice using a targeting DNA construct that replaced exon 5 encoding a CGRP-specific region [25]. C57BL/6 pure background mice were used for bone marrow transplantation (BMT) experiments.…”
Section: Animalsmentioning
confidence: 99%